Investments in the Intellectual Potential of Youth and Their Effect on Startups - Ahrorov Zarif Oripovich; Nosirov Bekhruzjon Zokirovich (International Journal on Economics, Finance and Sustainable Development, 2021)
At the moment, the focus is on startups as a manifestation of socio-economic development. This article analyzes the current situation with the implementation of startups and the role of youth in it, and develops recommendations for solving problems. This article justifies the need to provide young people with the necessary knowledge and skills in developing startups.